Correlations between neuropsychiatric symptoms and executive dysfunction in Alzheimer’s Disease - Sotomayor, Paloma A. (2007)
Objective: To explore the correlations between neuropsychiatric symptoms and executive dysfunction in Alzheimer’s Disease (AD). Patients and method: In a sample of 39 patients with AD the following instruments were used: the NeuroPsychiatric Inventory Questionnarie (NPI-Q) to assess the frequency of neuropsychiatric symptoms, the Frontal Assessment Battery (FAB)to assess executive dysfunction, and the Mini Mental State Examination (MMSE) to divide the sample into subgroups depending on level of cognitive impairment. Results: Negative correlations were found between prehension behavior and the frequency of euphoria/exaltation, sleep disorders, disinhibition and hallucinations. Unexpected positive correlations were also found between sensitivity to interference and hallucinations; motor sequences and disinhibition and eating disorders; verbal fluency and eating disorders; and Go-No go and euphoria/exaltation.